Clearance measurement for general steel waste. (15th June 2020) - Yokoyama, Kaoru; Ohashi, Yusuke
Highlights: Measurement tests for common steel materials were conducted using clearance verification system. The 1.001 MeV gamma rays emitted by 234m Pa and the associated scattered gamma rays were used to determine uranium. Relative errors were almost within 30% for 1 g of uranium. Abstract: A large amount of general steel waste is generated during decommissioning and dismantling of nuclear facilities. Very low contaminated radioactive waste, whose radioactivity is below clearance level, generated from the demolition process may be reused for general use. We examined the feasibility of the clearance verification system for uranium waste. The relative error of uranium determination was within 30 % for 1 g of uranium when measuring steel materials (angle bar, channel steel, pipe steel, square steel tube, fragments of steel tube).